THE NEUROSCIENCE IN PHYSICAL EDUCATION: BRAIN ACTIVITY OF STUDENTS IN RONDÔNIA (Fiep Bulletin - online, 2024)
Introduction: It is a consensus that physical exercise induces neuroplastic changes that are associated with improvements in cognitive functions. Objective: to draw a profile of brain activity through analysis of tests related to the variables: working memory, focused attention and mental processing speed; through EEG electroencephalography recordings the waveforms. Methods: the sample consisted of 23 students aged 10 to 12 years old from a public school. EEG was used to reveal changes in brain state. For the concentrated attention test, the grid test was used, for the memory test, the Digit span was used, and to analyze mental processing speed, the double-choice reaction time test was used. Results: the results showed that in the Delta and Theta frequency bands the highest activities in millivolts were recorded during rest. Working memory tests had an average of 4 numbers in the correct order. Regarding the concentrated attention test, the average was 9 points. Finally, the average time that students reacted to the stimulus was 384 milliseconds. Conclusion: the positive correlation indicates that an increase in Alpha activity probably occurred, producing an increase in the focused attention test scores. The negative correlation indicates that an increase in Beta 1 activity in area F7 likely promoted a decrease in motor reaction time, which means an increase in mental processing speed.
Keywords: Electroencephalogram; working memory; focused attention; processing speed